Family relationship, water contact and occurrence of Buruli ulcer in Benin. - Ghislain Emmanuel Sopoh; Yves Thierry Barogui; Roch Christian Johnson; Ange Dodji Dossou; Michel Makoutodé; Sévérin Y Anagonou; Luc Kestens; Françoise Portaels (Public Library of Science (PLoS), 2010)
BACKGROUND: Mycobacterium ulcerans disease (Buruli ulcer) is the most widespread mycobacterial disease in the world after leprosy and tuberculosis. How M. ulcerans is introduced into the skin of humans remains unclear, but it appears that individuals living in the same environment may have different susceptibilities. OBJECTIVES: This study aims to determine whether frequent contacts with natural water sources, family relationship or the practice of consanguineous marriages are associated with the occurrence of Buruli ulcer (BU). DESIGN: Case control study. SETTING: Department of Atlantique, Benin. SUBJECTS: BU-confirmed cases that were diagnosed and followed up at the BU detection and treatment center (CDTUB) of Allada (Department of the Atlantique, Benin) during the period from January 1st, 2006, to June 30th, 2008, with three matched controls (persons who had no signs or symptoms of active or inactive BU) for age, gender and village of residence per case. MAIN OUTCOMES MEASURED: Contact with natural water sources, BU history in the family and the practice of consanguineous marriages. RESULTS: A total of 416 participants were included in this study, including 104 cases and 312 controls. BU history in the family (p<0.001), adjusted by daily contact with a natural water source (p = 0.007), was significantly associated with higher odds of having BU (OR; 95% CI = 5.5; 3.0-10.0). The practice of consanguineous marriage was not associated with the occurrence of BU (p = 0.40). Mendelian disorders could explain this finding, which may influence individual susceptibility by impairing immunity. CONCLUSION: This study suggests that a combination of genetic factors and behavioral risk factors may increase the susceptibility for developing BU.